PENGEMBANGAN SISTEM MANAJEMEN SUMBER DAYA MANUSIA APARATUR PEMERINTAH DAERAH - Harry Suderajat (Jurnal Ilmu dan Budaya, 2010)
Human Resources is such an important part in an organization, includes regional government organization. This research used a comparison method between actual condition and Human Resources management ideal in strategic management perspective of Human Resources. The result is, so far, the management of Human Resources in regional government is still administrative and did not reach the strategic management of Human Resources, yet.